Anxiety Analysis of Students Taking Distance Learning in Mathematics Learning in Junior High Schools - Sara, Joanna Ayuni (Universitas Sebelas Maret, 2022)
Mathematics anxiety is a psychological condition of students in the learning process of mathematics. This study aims to describe students' learning anxiety in distance learning in mathematics learning. The method used in this study is a literature review method of books and literature as data. The method used in this study is a literature review method of books and literature as data. In addition, this research was strengthened by collecting data obtained through distributing questionnaires consisting of 17 statements in order to determine the interpretation of mathematics learning anxiety experienced by students in distance learning. Questionnaires were given to students at SMPTK Pelita Hati Denpasar in the 2021/2022 academic year as many as 27 respondents. The results of this study indicate that students experience learning anxiety in online mathematics learning. Forms of anxiety when participating in distance learning in mathematics learning that arise from students in the form of feelings of fear, worry, lack of confidence, anxiety, faster heart beats and even trying to avoid learning.